Legalitas Agama Menurut Ibn ‘Arabi - M. Mukhlis (Al-Jami'ah Research Centre, 2005)
In connection with the issues of religious pluralism, it is often that people have improper opinion on Ibn ‘Arabi. This article shows the thought of this prominent figure in religious pluralism, especially his concept in the parameter of religion, which he conceived in the construct of al-amr al-takwini and al-amr al-taklifi. In adition, the writer discusses Ibn ‘Arabi’s view on the superiority of Muhammad’s Islam among other religions, in spite of his pluralistic ideas.